Cannabidiol: main mechanisms of action and therapeutic targets - Klaudia Kowalczyk; Natalia Trąbka; Gabriela Demidowicz; Nina Lasota; Katarzyna Cichoń; Małgorzata Chyćko; Julia Czarnota; Wojciech Wiśniewski; Maciej Lambach; Martyna Younes (Kazimierz Wielki University, 2023)
Introduction: Over the past few years, multiple publications have proven many beneficial properties associated with CBD. Currently, its use in the treatment of inflammatory and autoimmune diseases is suggested. Also, very often the use of CBD in the treatment of anxiety disorders, schizophrenia and depression, as well as Parkinson's disease and Alzheimer's disease is the subject of scientific research. CBD could be also used in treatment of the chronic pain in cancer patients or in people with diabetic complications. So far, it has been proven that CBD has anti-inflammatory, anticonvulsant, antioxidant, anti-arthritic, procognitive, cardio- and neuroprotective effects. The potential of cannabidiol in the prevention and treatment of many diseases is seen in its complex and multidirectional mechanisms of action. CBD has low affinity for cannabinoid receptors and acts as an inverse agonist of type 2 cannabinoid receptors (CB2-R). Additionally, CBD exerts its effects through many other molecular targets. Aim of the study: The aim of this review is to present mechanisms of action of cannabidiol and its possible therapeutic targets. Materials and methods: The literature available in the PubMed and Google Scholar data bases was reviewed, using the following keywords: "cannabidiol", "CBD", "CBD's mechanism of action", "CBD therapeutic targets", "endocannabinoid system". Conclusions: Cannabidiol is a promising candidate in the treatment of many common diseases. Furthermore, research is needed to confirm its beneficial effects and turn it into an effective drug that supports therapy with other drugs.